2009
DOI: 10.1007/s11306-009-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Negative mode nanostructure-initiator mass spectrometry for detection of phosphorylated metabolites

Abstract: The chemical complexity of the metabolome requires the development of new detection methods to enlarge the range of compounds detectable in a biological sample. Recently, a novel matrix-free laser desorption/ ionization method called nanostructure-initiator mass spectrometry (NIMS) [Northen et al., Nature 449(7165):1033-1036, 2007 was reported. Here we investigate NIMS in negative ion mode for the detection of endogenous metabolites, namely small phosphorylated molecules. 3-Aminopropyldimethylethoxysilane was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…A number of analytical approaches were developed with detection limits low enough for single-cell metabolite analyses [e.g., nanostructured surfaces (7,8), postionization techniques (9,10), modified laser optics (11), the use of microsampling tools (12,13), microarrays for MS measurements (14,15), etc.]. Until now, however, most MS studies targeting single-cell metabolite analysis have only shown the analytical capabilities, but have not demonstrated that true biological information can be retrieved from studying the metabolism of single cells.…”
mentioning
confidence: 99%
“…A number of analytical approaches were developed with detection limits low enough for single-cell metabolite analyses [e.g., nanostructured surfaces (7,8), postionization techniques (9,10), modified laser optics (11), the use of microsampling tools (12,13), microarrays for MS measurements (14,15), etc.]. Until now, however, most MS studies targeting single-cell metabolite analysis have only shown the analytical capabilities, but have not demonstrated that true biological information can be retrieved from studying the metabolism of single cells.…”
mentioning
confidence: 99%
“…This versatility is a particularly powerful characteristic of NIMS surface that expands the range of detectable metabolites and, consequently, extract the maximum information from chemical complex samples. For instance, Zenobi and co-workers [24] demonstrated that compounds containing amino groups as initiators promoted the formation of ions in negative ionization mode, which suggests that the basicity of the initiator could assist the ionization process. By using 3-aminopropyldimethylethoxysilane (APDMES) as initiator, they detected phosphorylated metabolites in the femtomole range.…”
Section: Nims Surface Modificationsmentioning
confidence: 99%
“…However, analysis of biofluids with negative-ion mode is possible with NIMS when a compatible pre-etch cleaning method or initiator material is used 35,36. When the highly acidic “Piranha solution” (sulfuric acid/hydrogen peroxide) was replaced with methanol as the pre-etch cleaning solvent, fatty acids were readily detected from a complex biofluid with NIMS 35.…”
Section: Nims Analysis Of Complex Biofluidsmentioning
confidence: 99%